Proviral-activated c-erbB is leukemogenic but not sarcomagenic: characterization of a replication-competent retrovirus containing the activated c-erbB. - Pelley, R J (1988)
Avian leukosis virus (ALV) induces erythroblastosis in chickens by integrating its DNA into the host c-erbB locus and by activating expression of truncated c-erbB transcripts. Although there is a 100% correlation of c-erbB activation with ALV-induced erythroblastosis, direct evidence that the activated c-erbB is oncogenic has not been established. We have constructed a replication-competent retrovirus containing the activated c-erbB to investigate its transforming potential. The Rous c-erbB virus (REB-c) was constructed by inserting the activated c-erbB cDNA into a Rous sarcoma virus vector in place of src. When transfected into transformed quail fibroblasts (QT6), the REB-c construct stably integrates and expresses c-erbB-specific transcripts and produces infectious virus. The REB-c retrovirus produces short-latency polyclonal erythroblastosis in chickens. However, in contrast to avian erythroblastosis virus which contains v-erbB, the REB-c construct does not transform chicken embryo fibroblasts in vitro, nor does the REB-c virus produce sarcomas when injected into the wing web of chickens. Our results provide the first direct evidence that the activated c-erbB which lacks the amino-terminal extracellular domain but which retains the entire carboxy-terminal sequences is leukemogenic but not sarcomagenic.